(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Kalidasa is India’s greatest Sanskrit poet and dramatist. In spite of the celebrity of his name, the time when he flourished always has been an unsettled question, although most scholars nowadays favor the middle of the 4th and early 5th centuries A.D., during the reigns of Chandragupta II Vikramaditya and his successor Kumaragupta. Undetermined also is the place of Kalidasa’s principal literary activity, as the frequent and minute geographic allusions in his works suggest that he traveled extensively.